Representasi Kulit Putih sebagai Standar Kecantikan Perempuan di Indonesia dalam Iklan Scarlett Whitening - Kumara, Anindya Listya; Zahira, Nathania; Sudiwijaya, Erwan (Jurnal Audiens, 2025)
The research aims to determine how white skin is represented in Scarlett Whitening advertisements. This research uses Roland Barthes' semiotic method. This research utilizes the theory of representation and beauty standards in media. The findings of this study are that in Scarlett Whitening advertisements; the representation of white skin becomes the standard of female beauty in Indonesia. This is evident from, first, the myth of Indonesian women's beauty is standardized in the form of a slender female body with white facial and body skin. Second, the myth that skin color changes require time and consistent care. This creates unrealistic expectations because it ignores the fact that skin color change requires a process and consistent care over a certain period. Third, the use of Korean girl bands as models suggests that the beauty standards being promoted are global beauty standards influenced by the South Korean entertainment industry. The use of Korean girl band models reflects how local beauty standards have been influenced by the globalized South Korean entertainment industry.